2013
DOI: 10.1371/journal.pone.0053995
|View full text |Cite
|
Sign up to set email alerts
|

The NHV Rehabilitation Services Program Improves Long-Term Physical Functioning in Survivors of the 2008 Sichuan Earthquake: A Longitudinal Quasi Experiment

Abstract: BackgroundLong-term disability following natural disasters significantly burdens survivors and the impacted society. Nevertheless, medical rehabilitation programming has been historically neglected in disaster relief planning. ‘NHV’ is a rehabilitation services program comprised of non–governmental organizations (NGOs) (N), local health departments (H), and professional rehabilitation volunteers (V) which aims to improve long-term physical functioning in survivors of the 2008 Sichuan earthquake. We aimed to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 29 publications
2
60
0
Order By: Relevance
“…[36,37] Disaster management experts believe that physical and physiological rehabilitation should be immediately started after response phase to disaster and it should continue in the community over the long term in order to improve and restore function of vulnerable peoples. [13,38,39] One of the studies emphasized social rehabilitation of vulnerable groups in order to ensure the participation of vulnerable groups in the planning and implementation World J Emerg Med, Vol 8, No 4, 2017 (2) intent to delegate responsibility; and (3) desire for a wide scope of social support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[36,37] Disaster management experts believe that physical and physiological rehabilitation should be immediately started after response phase to disaster and it should continue in the community over the long term in order to improve and restore function of vulnerable peoples. [13,38,39] One of the studies emphasized social rehabilitation of vulnerable groups in order to ensure the participation of vulnerable groups in the planning and implementation World J Emerg Med, Vol 8, No 4, 2017 (2) intent to delegate responsibility; and (3) desire for a wide scope of social support.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of them also did not consider important confounding factors. None of the randomized controlled trial articles reported blinding of participants or assessors and two studies [35,36] lacked a control group. More details have shown in Table 1.…”
Section: Database Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…The NHV model also provided community-based rehabilitation and included a rehabilitation training and qualification program for local professionals, as well as tools for patient management and education. 28 Foreign medical teams (for example, Taiwan, Russia, Hong Kong, Japan, Italy, Germany, France, UK, USA and Cuba) spent 3 weeks in Sichuan, treating 24 410 cases at 11 sites, which included surgical and nursing care 29 as well as rehabilitative post-surgical care. Training of host medical services was also provided.…”
Section: Selected Data From Recent Severe Eqsmentioning
confidence: 99%